2021
DOI: 10.1002/jobm.202100335
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the halotolerance of a Bacillus serine protease by protein surface engineering

Abstract: A moderately halotolerant serine protease was previously isolated from Bacillus subtilis from salted, fermented food. Eight mutation sites on the protein surface were selected for protein engineering based on sequence and structural comparisons with moderately halotolerant proteases and homologous non-halotolerant proteases. The newly constructed multiple mutants with substituted Asp and Arg residues were compared with the recombinant wild type (rApr) and the previously constructed mAla-8 substituted with Ala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…BPN' has five of the seven amino acid positions identified by Takenaka et al. [ 86 ] as favorable for salt adaptation and therefore, unlike subtilisin Carlsberg, shows good adaptation to high salt concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BPN' has five of the seven amino acid positions identified by Takenaka et al. [ 86 ] as favorable for salt adaptation and therefore, unlike subtilisin Carlsberg, shows good adaptation to high salt concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…4), and in general, a high proportion of negative or positive charges on the surface of the enzyme improves salt adaptation [86]. BPN' has five of the seven amino acid positions identified by Takenaka et al [86] as favorable for salt adaptation and therefore, unlike subtilisin Carlsberg, shows good adaptation to high salt concentrations.…”
Section: Effect Of Sds and H 2 O 2 On Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the true subtilisins studied here, BPN′, which belongs to the same subgroup, showed higher activity with increasing NaCl levels (Falkenberg et al 2022b ). This is probably because BPN′ has five of the seven amino acid positions identified that are beneficial for salt adaptation (Takenaka et al 2022 ). The finding that SPAH lost more activity at higher NaCl concentrations could be related to the constant activity at high salt concentrations and thus a higher autoproteolytic activity, which was also observed for subtilisin Carlsberg (Falkenberg et al 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…3 ). As mentioned above, salt adaptation is increased by a high number of negative or positive charges on the surface of the enzyme (Takenaka et al 2022 ). The differences in the AB ratio of all residues seems to have no influence on the salt tolerance, as the AB ratio of SPPM (1.9) and SPAH (1.7) is quite high, but much lower for SPMI (1.0) and SPLA (1.1) (Fig.…”
Section: Discussionmentioning
confidence: 99%